Cytomegalovirus esophagitis in an immunocompetent patient: Case report - Lim, Dae Seop; Lee, Tae Hee; Jin, So Young; Lee, Joon Seong (Turkish Journal of Gastroenterology, 2014)
Abstract Cytomegalovirus (CMV) esophagitis is well-documented in immunocompromised patients. A few studies have described CMV infection in immunocompetent patients diagnosed with a critical illness. However, CMV esophagitis has rarely been documented in immunocompetent hosts. We report a case of CMV esophagitis in an immunocompetent patient who presented with chest pain and dysphagia that was successfully resolved with ganciclovir treatment. Our case supports observations that CMV esophagitis can cause significant morbidity, regardless of immune system status.